1975
DOI: 10.1021/bi00684a026
|View full text |Cite
|
Sign up to set email alerts
|

Circular dichroism and fluorescence studies on the binding of ligands to the α subunit of tryptophan synthase

Abstract: Binding to the alpha subunit of tryptophan synthase induces extrinsic Cotton effects in the substrates indole (IND), indoleglycerol phosphate (IGP), and D-glyceraldehyde-3-P (D-GAP) and in the inhibitor indolepropanol phosphate (IPP). These effects disappear when the enzyme is denatured in guanidinium chloride. The induced circular dichroism (CD) was used to determine the dissociation constant and the number of binding sites for IPP. The dissociation constant so determined is equal to 48 muM and is in good agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0

Year Published

1976
1976
2001
2001

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 20 publications
5
40
0
Order By: Relevance
“…Nonspecific binding signals measured as ␣ 2 ␤ 1 binding to the blocking agent BSA were subtracted from the binding values for ␣ 2 ␤ 1 binding to native and denatured rhodocetin, respectively. The titration curves were linearized, and a K d value was determined according to the algorithm given by Heyn and Weischet (22).…”
Section: Methodsmentioning
confidence: 99%
“…Nonspecific binding signals measured as ␣ 2 ␤ 1 binding to the blocking agent BSA were subtracted from the binding values for ␣ 2 ␤ 1 binding to native and denatured rhodocetin, respectively. The titration curves were linearized, and a K d value was determined according to the algorithm given by Heyn and Weischet (22).…”
Section: Methodsmentioning
confidence: 99%
“…inset Fig.2). Indolepropanol phosphate binds to the active site of the a-subunit [6,7]. Since the active site is likely to bind the substrate indole, albeit weakly, the simplest interpretation of the interaction between indolepropanol phosphate and indole binding to the sites of low affinity is direct competition.…”
Section: Data Evaluationmentioning
confidence: 99%
“…The inhibition towards indole is probably non-competitive, although competition cannot be strictly excluded. Moreover spectrophotometric titrations employing circular dichroism have shown that D-glyceraldehyde 3-phosphate binds to the free a subunit [7]. In contrast the enzyme has only weak affinity for indole at the active center [6].…”
Section: The Mechanismmentioning
confidence: 99%
“…In the case of indoleglycerol phosphate synthesis this hypothesis is supported by the following additional evidence. Circular dichroism studies have shown that aromatic amino acid sidechains of the a subunit are perturbed by bound glyceraldehyde 3-phosphate [7]. Moreover, the binding of indolepropanol phosphate to either the a subunit or to the a2p2 complex of tryptophan synthase appears to be accompanied by conformational changes 15 -7, 28,291.…”
Section: Local and Gross Conformational Changesmentioning
confidence: 99%